2014
DOI: 10.1111/neup.12132
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of fatty acid synthase and nuclear localization of carnitine palmitoyltransferase 1C are common among human gliomas

Abstract: Fatty acid synthase (FASN) and carnitine palmitoyltransferase 1C (CPT1C), a brain-specific isoform of the CPT1 family, are upregulated in certain types of cancers, including gliomas. Acetyl-CoA carboxylase (ACC) catalyzes the carboxylation of acetyl-CoA to malonyl-CoA, the rate-limiting step in fatty acid synthesis, and its phosphorylated form inhibits lipid synthesis. We examined the expression and subcellular localization of these fatty acid metabolism-related molecules in human gliomas. We performed immunos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 29 publications
(42 reference statements)
4
20
0
Order By: Relevance
“…Therefore, it is suggested that CPT1C promotes cancer cell survival and tumor growth and it has been proposed as a new therapeutic target in cancer treatment. It is noteworthy that recent studies report an aberrant expression of CPT1C in gliomas (Cirillo et al, 2014 ; Wakamiya et al, 2014 ). These findings highlight the importance of unraveling the molecular mechanisms of CPT1C, which could be of great interest across a range of fields, for example in the study of new anticancer therapies and new diagnostic or prognostic markers.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, it is suggested that CPT1C promotes cancer cell survival and tumor growth and it has been proposed as a new therapeutic target in cancer treatment. It is noteworthy that recent studies report an aberrant expression of CPT1C in gliomas (Cirillo et al, 2014 ; Wakamiya et al, 2014 ). These findings highlight the importance of unraveling the molecular mechanisms of CPT1C, which could be of great interest across a range of fields, for example in the study of new anticancer therapies and new diagnostic or prognostic markers.…”
Section: Discussionmentioning
confidence: 96%
“…For 18 F-FPA, the ratio of tumor-to-inflammation was lower than that of 18 F-FDG (Table 1 ), but the higher selectivity indices of tumor-to-inflammation (muscle or blood corrected ratios of tumor-to-inflammation, 3.52 ± 0.13 or 8.00 ± 1.37) were observed. The significant uptake of 18 F-FAC and 18 F-FPA in the inflammatory lesions might be attributed to the high expression of the acetyl- or propionyl-CoA synthetases and fatty acid synthnase in these tissues [ 34 36 ]. In addition, the higher uptake of 18 F-FAC and 18 F-FPA were observed in the lower part of the gut, which was a result of the re-absorption of small carboxylic acids occurrence [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that CPT1C is involved in ceramide metabolism in normal neuronal cells [47] and that CPT1C deficiency in embryonic stem cells causes the accumulation of specific species of longchain FAs, among them arachidonic acid [31], suggest that CPT1C affects additional, as yet undefined, pathways. Moreover, recent studies performed by Wakamiya et al [125] showed that a truncated form of CPT1C is located in the nuclei of diffuse gliomas of…”
Section: Cpt1c In Tumor Cellsmentioning
confidence: 99%